Breast Cancer After Treatment of Differentiated Thyroid Cancer With Radioiodine in Young Females: What We Know and How to Investigate Open Questions. Review of the Literature and Results of a Multi-Registry Survey - Reiners, Christoph; Schneider, Rita; Platonova, Tamara; Fridman, Mikhail; Malzahn, Uwe; Mäder, Uwe; Vrachimis, Alexis; Bogdanova, Tatiana; Krajewska, Jolanta; Elisei, Rossella; Vaisman, Fernanda; Mihailovic, Jasna; et al. (Frontiers in Endocrinology, 2020)
Published studies on the risk of radiation-induced second primary malignancy (SPM) after radioiodine treatment (RAI) of differentiated thyroid cancer (DTC) refer mainly to patients treated as middle-aged or older adults and are not easily generalizable to those treated at a younger age. Here we review available literature on the risk of breast cancer as an SPM after RAI of DTC with a focus on females undergoing such treatment in childhood, adolescence or young adulthood. Additionally, we report results of a preliminary international survey of patient registries from academic tertiary referral centers specializing in pediatric DTC. The survey sought to evaluate the availability of sufficient patient data for a potential international multicenter observational case-control study of females with DTC given RAI at an early age. Our literature review identified a bi-directional association of DTC and breast cancer. The general breast cancer risk in adult DTC survivors is low, 2%, slightly higher in females than in males, but presumably lower, not higher, in those diagnosed as children or adolescents than in those diagnosed at older ages. RAI presumably does not substantially influence breast cancer risk after DTC. However, data from patients given RAI at young ages are sparse and insufficient to make definitive conclusions regarding age-dependence of the risk of breast cancer as an SPM after RAI of DTC. The preliminary analysis of data from 10 thyroid cancer registries worldwide, including altogether 6,449 patients given RAI for DTC and 1,116 controls, i.e., patients not given RAI, did not show a significant increase of breast cancer incidence after RAI. However, numbers of cases and controls were insufficient to draw statistically reliable conclusions, and the proportion of those receiving RAI at the earliest ages was too low. In conclusion, a potential international multicenter study of female patients undergoing RAI of DTC as children, adolescents or young adults, with a sufficient sample size is feasible. However, breast cancer screening of a larger cohort of DTC patients is not unproblematic for ethical reasons, due to the likely at most slightly increased risk of breast cancer post-RAI and the expected 10% false-positivity rate potentially producing substantial “misdiagnosis”.